Enhancing Genetic Gain in Potato Clones through Phenotyping Late Blight Resistance - Subedi, Subash; Tripathi, Niru; Neupane, Saraswati; Bastakoti, Puja (Talenta Publisher, 2021)
Late blight, caused by Phytophthora infestans (Mont.) de Bary, is a devastating disease of potato (Solanum tuberosum L.). To identify potential sources of resistance to the disease, 32 clones received from the National Potato Research Program (NPRP) were evaluated under natural conditions at the National Maize Research Program Rampur, Chitwan in 2018 and 2019. Potato cultivars Desire, Kufri Jyoti, and Farmers local were used as moderately resistant, susceptible, and highly susceptible checks, respectively. The experiments were laid out in Î±-lattice design with two replications. Each experimental plot of 3.6 m2 was seeded as two 3m long rows with 0.6 and 0.25 m row and plant spacing, respectively. Agronomic practices were followed as recommended by NPRP. The disease severity was measured based on a percentage of leaf area infected using disease scale of (1 to 9) at three times in seven days intervals. Disease severity values were converted into the area under disease progress curve (AUDPC). During harvest, the total yield and its components were recorded. Potato clones differed significantly (P â‰¤ 0.01) for disease severity, yield, and yield components. The results revealed high genetic variability, heritability, and genetic gain for disease parameters, tuber yield, and its components. Six clones (CIP311622.9, PRP277072.122, PRP146971.135, PRP147072.27, CIP311350.27, and PRP146971.117 had lower area under disease progress curve AUDPC) values (274.25 to 421.03), showed higher resistant in both years and yielded more tuber yield ( 20 t/ha) than other clones. These clones could be used to develop late blight resistant, high yielding potato varieties